Style ojcostwa w trylogii znad rozlewiska Małgorzaty Kalicińskiej - Bolińska, Marta (Wydawnictwo Naukowe EDUsfera, 2022)
The article introduces a typology of styles of fatherhood, primarily from a pedagogical and cultural perspective, and presents selected creations of fatherhood in the literary space. An example of a fictional, multifaceted, historically, and culturally transforming image of fatherhood is the trilogy by Małgorzata Kalicińska: "House by the Backwater","Returns the Backwater" and "Love over the Backwater".
Keywords: historia; ojciec; style ojcostwa; trylogia mazurska; saga rodzinna; kultura